2017
DOI: 10.1016/j.sjbs.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenotypic and PCR methods for detection of carbapenemases production by Enterobacteriaceae

Abstract: Dissemination of carbapenem resistance via Enterobacteriaceae, particularly among and, is a major public health concern. Rapid methods for determining antimicrobial susceptibility are important to ensure adequate and appropriate use of antimicrobial agents and to limit the spread of these bacteria. In the current study, we compared the rapidity, sensitivity and specificity of traditional methods and molecular-based Xpert Carba-R PCR assay to identify sixty isolates, (26 and 34). The specificity of MicroScan wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
8
26
2
Order By: Relevance
“…The current study revealed the superiority of MHT over Carba NP test for detection of carbapenemases, this finding was also reported by a recent Egyptian study 35 that showed a high sensitivity for MHT in which 100% (14/14) of CRKP isolates, that were molecularly confirmed to be carbapenemase producers, were tested positive for MHT. Similar findings were reported by AlTamimi et al 40 who found that the sensitivity of MHT among CRKP isolates was 92% (23/25). In the current study, we supposed that the negative MHT result for the five isolates that genotypically tested positive for carbapenemases may be due to false negatives rather than true negatives.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study revealed the superiority of MHT over Carba NP test for detection of carbapenemases, this finding was also reported by a recent Egyptian study 35 that showed a high sensitivity for MHT in which 100% (14/14) of CRKP isolates, that were molecularly confirmed to be carbapenemase producers, were tested positive for MHT. Similar findings were reported by AlTamimi et al 40 who found that the sensitivity of MHT among CRKP isolates was 92% (23/25). In the current study, we supposed that the negative MHT result for the five isolates that genotypically tested positive for carbapenemases may be due to false negatives rather than true negatives.…”
Section: Discussionsupporting
confidence: 91%
“…Of the detected OTCs, OXA-48 was the most prevalent one in which 73.68% (14/19) of isolates were found to harbor bla OXA-48 . Similar findings were reported by the Turkish, 43 Egyptian, 31 and Saudi 40,44 studies that reported that bla OXA-48 was more prevalent in CRKP clinical isolates.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies conducted by Al Tamimi et al . and ElMahallawy et al ., had reported (43%) and(49%), respectively with the MHT results [ 27 28 ]. In the current study, relatively low percentage of carbapenemase detection by MHT could be attributed to presence of class B carbapenemase including NDMs, VIMs and IMPs that requires zinc for their action[ 22 ].…”
Section: Discussionmentioning
confidence: 94%
“…These include Xpert Carba-R (Cepheid), Check-Direct CPE (Check-Points Health), and an antibiotic resistance TaqMan assay (ThermoFisher Scientific). Xpert Carba-R is a fully automated and integrated system for sample preparation, DNA extraction, amplification, and qualitative detection of target genes using multiplex real-time PCR assays with a Ͻ1-h turnaround time (214). The method can be used directly on swab specimens and has 96.6% sensitivity and 98.6% specificity (215).…”
Section: Detection Of Ndm-encoding Genesmentioning
confidence: 99%